2013
DOI: 10.1068/p7409
|View full text |Cite
|
Sign up to set email alerts
|

Recovering 3-D Shape: Roles of Absolute and Relative Disparity, Retinal Size, and Viewing Distance as Studied with Reverse-Perspective Stimuli

Abstract: When viewing reverspective stimuli, data-driven signals such as disparity, motion parallax, etc, help to recover veridical three-dimensional (3-D) shape. They compete against schema-driven influences such as experience with perspective, foreshortening, and other pictorial cues that favor the perception of an illusory depth inversion. We used three scaled-size versions of a reverspective to study the roles of retinal size, binocular disparity, and viewing distance--that influences both vergence and accommodatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…While this codependence of multiple depth cues on distance complicates interpretation of flipping distance, differences between viewing conditions can be used to infer whether or not a manipulated source of depth information helps disambiguate the illusion. Work with reverspectives shows that viewing distance, rather than the absolute disparity magnitudes, is critical in determining reversibility ( Dobias & Papathomas, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…While this codependence of multiple depth cues on distance complicates interpretation of flipping distance, differences between viewing conditions can be used to infer whether or not a manipulated source of depth information helps disambiguate the illusion. Work with reverspectives shows that viewing distance, rather than the absolute disparity magnitudes, is critical in determining reversibility ( Dobias & Papathomas, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely, however, that this small 4.5% decrease in viewing distance was responsible for the significant decrease in illusion strength, which was 35.4% (0.42–0.65)/0.65] for the painted and 49.1% (0.27–0.53)/0.53] for the unpainted stimuli in this experiment. For comparison, Dobias and Papathomas (2013) reported that decreasing the viewing distance by a factor of 50% (from 535 to 267.5 cm) for the same painted stimulus used in the present experiment, decreased the illusion strength by only 14.7%. Thus, the difference in illusion strength is likely due, to a major extent, to the convexity bias.…”
Section: Discussionmentioning
confidence: 51%
“…When fixating the “water” mark at the top of the truncated pyramid, which is at 256 (268−12) cm, the distance from the observer is about 4.5% shorter than when fixating the central building corner (at 268 cm). The strength of reverse-perspective illusions has been shown to decrease as the viewing distance decreases ( Dobias & Papathomas, 2013 ; Papathomas, 2002 ; Rogers & Gyani, 2010 ). It is unlikely, however, that this small 4.5% decrease in viewing distance was responsible for the significant decrease in illusion strength, which was 35.4% (0.42–0.65)/0.65] for the painted and 49.1% (0.27–0.53)/0.53] for the unpainted stimuli in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of depth cues in perceiving reverspectives is a key question in this area. Thus far, the main cues that have been studied are binocular disparity, linear perspective and motion parallax [5,33,34]. It appears that prior experiences, specifically with retinal perspective projection, play a leading role in the depth-inversion illusion.…”
Section: The Influence Of Prior Experiences On Visual Perceptionmentioning
confidence: 99%